Structure and organizational design of fenavi, central sectional (2020)
The collective work of second semester, is a research project which allows that theory learned at the subjects involved, is applied to the field activity. This work will be done around the “structure and organizational design of small and medium organizations”, in order to apply the concepts and theories saw in class, focusing in matters like: accounting and organization theories, besides that, this project was formulated with solid knowledge about investigation process. In this order of ideas, there are understood the processes to make reference to what research is, which are the paradigms and standards to execute that information that will be necessary for the development of this collective work. The research process was focused on the observation and analysis of a regional company, in this case will be FENAVI (by its acronyms In Spanish for Federación Nacional de Avicultores de Colombia), but mainly of its central section, located in the city of Pereira. This with the target of identify the structure and organizational design. In order to make it, there was made a state of art that consists basically in checking and recognizing the main authors that have raised knowledge about the subject in matter and based on those, it can consolidate similarities between the theories seen on those backgrounds that allows to see possibilities about the formulated question. This way, there will be an “x-ray” of the FENAVI Company, starting from general to expand the information to get FENAVI central section.